Competitiveness of dairy industry companies operating in sustainable development conditions - Hadryjańska, Barbara (Journal of agribusiness and rural development, 2017)
The aim of this study is to present issues connected with introduction of the sustainable development concept in range of the environmental aspect in companies operating in the dairy industry, and to show how such activities affect competitiveness of those subjects. A description of environmental measures taken in companies the dairy industry situated in the entire country was made. These activities have been related to reducing water consumption and sewage production, reducing the amount of waste produced and reducing the amount of dust and gaseous pollutants. This study attempts to find relations describing those measures including change in the competitive position of investigated companies. It turned out, that those relations are not equal with reference to all environmental changes introduced in the manufacturing companies. Some part of pro-environmental measures have beneficial effects on the financial result or in company’s market share, and some of those measures do not show any relation or they even sometimes show a negative relation.